Higher dietary insulinemic potential is associated with kidney stones: a nationally representative cross-sectional study - Bao Zhang; Mengsha Tang; Xiude Li (Nutrition Journal)
Abstract Background Insulin response may significantly contribute to the formation of kidney stones. Diets can modulate the insulin response and we hypothesize that high insulinemic potential diets may increase the kidney stones risk. Methods Data were from the US National Health and Nutrition Examination Survey. Diets were assessed by 24-hour dietary recall. Two empirical dietary indices for insulin resistance (EDIR) and hyperinsulinemia (EDIH) were used to reflect the dietary insulinemic potential. Diagnosis of kidney stones was based on self-report. Logistic regression was employed to calculate ORs and 95% CIs while adjusting for variables identified through a directed acyclic graph (DAG). Results Higher EDIR [OR Tertile 3 vs. Tertile 1 = 1.31 (95% CI: 1.13–1.53); OR Per−standard deviation increase = 1.11 (95% CI: 1.05–1.18); p trend = 0.001] and EDIH [OR Tertile 3 vs. Tertile 1 = 1.26 (95% CI: 1.08–1.47); OR Per−standard deviation increase = 1.10 (95% CI: 1.04–1.16); p trend = 0.001] scores were both positively associated with kidney stones. The conclusion remains unchanged in the sensitivity analysis after adjusting for potential mediating factors that were identified from the DAG, including BMI, hypertension, and diabetes. Subgroup analysis showed that results in most subgroups were consistent with the main analysis. Conclusions This study indicates that the insulinemic potential of diet may partly underlie the influence of dietary patterns on kidney stones, emphasizing the importance of avoiding dietary patterns with insulinemic potential. Clinical trial number Not applicable.